1676. Evaluation of Antibiotic Overuse for Asymptomatic Bacteriuria in a Hospital with Low Baseline Antibiotic Use. (31st December 2020) - Kernan, Bailey; Shihadeh, Katherine C; Jenkins, Timothy C
Abstract: Background: In 2019, the Infectious Diseases Society of America published guidelines for the management of asymptomatic bacteriuria (ASB) with recommendations to avoid antimicrobial therapy in most patients. Denver Health has existing guidance for the management of patients with a urinary tract infection (UTI) and in August of 2019, implemented specific guidance for the management of ASB. As an institution, Denver Health has a Standardized Antimicrobial Administration Ratio (SAAR) of 0.8-0.9, suggesting a strong antimicrobial stewardship program with a ratio of < 1. The purpose of this study is to assess if signs and symptoms were present in patients prescribed an antibiotic for UTI. Methods: We retrospectively identified hospitalized patients at least 18 years old who were prescribed an antibiotic with "UTI" as the indication from March 1 st to August 31 st, 2019. Patients with catheter-associated UTIs were excluded. A random sample of 50 cases was manually reviewed for signs and symptoms of infection. Signs were considered fever, defined as at least 38 o C or leukocytosis, defined as at least 10 k/uL WBC. Symptoms collected were based on documentation of patient reported dysuria, frequency, or urgency, or findings of hematuria. The primary outcome was proportion of patients prescribed an antibiotic for UTI in the absence of signs or symptoms. Prescribing patterns for choice and duration of antimicrobials were also surveyed. Results: A total of 382 antibiotics were prescribed for UTI during the study period. Of the 50 cases reviewed, median age was 65.8 years, with 11% being male. Overall, 29 patients (58%) had no documented symptoms while being treated for UTI. Additionally, 22 patients (44%) had no documented fever, leukocytosis, or urinary symptoms. The most commonly prescribed antibiotics were cefdinir, fosfomycin, and nitrofurantoin. Tables 1 and 2 include additional findings. Table 1 Symptomology and Type of UTI Table 2 Antimicrobial Choice and Duration Conclusion: Despite a well established stewardship program, nearly half of patients prescribed an antibiotic for UTI did not have signs or symptoms consistent with infection. This suggests many patients were treated for ASB, without necessity. Among hospitals with comparatively low antibiotic use, ASB may be a high-yield opportunity to reduce unnecessary antibiotic use. Disclosures: All Authors : No reported disclosures